Pengaruh Teh DBW (Daun Belimbing Wuluh) Terhadap Penurunan Kadar Gula Darah Pada Penderita Diabetes Melitus di Wilayah Kerja Puskesmas Kadudampit - Anggrum Widya Lestari; Burhanuddin Basri; Arfatul Makiyah (Jurnal Ventilator, 2024)
Background: Diabetes is a chronic metabolic disorder characterized by high blood glucose levels and accompanied by disorders of carbohydrate, lipid and protein metabolism as a result of insufficient insulin function. Diabetes is a chronic disease characterized by blood glucose levels that exceed normal values (hyperglycemia). Research Objective: To determine the effect of DBW (Wuluh Starfruit Leaves) tea on reducing blood sugar levels in diabetes mellitus sufferers in the Kadudampit Community Health Center working area. Research Method: The research design used is Quasi Experimental research with a one group pretest-posttest design approach. The number of respondents was 16 respondents. The data collection technique used non-probability sampling technique with purposive sampling type. Results: the results of statistical tests using the Paired Samples Test, the resulting P value was 0.001 < 0.05. Conclusion: There is an effect of giving DBW (Starfruit Leaf) tea on reducing blood sugar levels in Diabetes Mellitus sufferers in the Kadudampit Community Health Center working area. Suggestion: It is hoped that the results of the research conducted can be used as information regarding complementary therapies, namely Starfruit Leaf tea, one of the complementary therapies for Diabetes Mellitus sufferers.